1996
DOI: 10.1016/s0886-3350(96)80152-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined cataract and glaucoma procedures using temporal cataract surgery

Abstract: Separating the cataract and glaucoma procedures frees the surgeon to use newer astigmatically neutral techniques for the cataract incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Postoperative complications in the control group were mainly fibrin reaction and insufficient filtering bleb (scarring or leakage), which is in line with the literature on the subject [8,9,10,20,23]. Although IOP reduction was sufficient 1 year after operation, numerous reoperations were necessary.…”
Section: Discussionsupporting
confidence: 84%
“…Postoperative complications in the control group were mainly fibrin reaction and insufficient filtering bleb (scarring or leakage), which is in line with the literature on the subject [8,9,10,20,23]. Although IOP reduction was sufficient 1 year after operation, numerous reoperations were necessary.…”
Section: Discussionsupporting
confidence: 84%
“…8 Another study on patients with combined operation with phacoemulsification technique reported a final WTR astigmatism of +0.49 dioptre. 9 In that study, the corneoscleral incision was enlarged to 6.0 mm for inserting the nonfoldable IOL and mitomycin C was not used in all eyes. In the current study, a 3 mm temporal corneal incision was created for phacoemulsification, a single interrupted suture was used to close the corneal incision, and mitomycin C was used in all but one patient who had very thin conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have also shown that there is induced corneal astigmatism after trabeculectomy and combined operation with various surgical techniques. [3][4][5][6][7][8][9] According to an evidence based review of the surgical techniques and adjuvant used in combined operation, the strongest evidence of efficacy exists for using mitomycin C, separating the incisions for cataract and glaucoma surgery, and removing the nucleus by phacoemulsification. 10 It is unclear whether combined operation with this technique will induce a change of AL and corneal astigmatism, and affect the postoperative refraction.…”
mentioning
confidence: 99%
“…The management of concurrent cataract and glaucoma remains a subject of controversy [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], partly because of a lack of convincing evidence for the superiority of any one surgical approach. Relevant factors that aid the ophthalmologist in deciding between therapeutic options include the level of intraocular pressure (IOP) control, the amount of glaucomatous optic neuropathy, the number of glaucomatous medications required, the visual severity of the cataract, and the compliance and general health of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, performing cataract and glaucoma surgery at the same time eliminates the extra morbidity and cost associated with successive operations and results in faster rehabilitation. Small-incision phacoemulsification with foldable intraocular lens (IOL) implantation has several theoretical advantages over extracapsular cataract extraction, including more rapid visual recovery, less induced astigmatism, shorter surgery time, and greater intraoperative control [5][6][7][8][9][10][11][12][13][14][15][16][17]. Besides, small-incision glaucoma triple procedure also reduces the risk of the transient IOP spikes that often occur after cataract surgery, especially in glaucoma patients [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%